Nurses' and Mental Health Technicians' Attitudes and Social Acceptance of People with Mental Illness. (27th September 2020) - Jacq, Krystyna de; Norful, Allison A.; Larson, Elaine
Abstract: Over 43 million Americans are diagnosed with a mental illness. Various factors, including health professionals' attitudes, prevent patients from seeking care. Previous evidence fails to identify nursing staff attitudes toward patients with mental illness. This cross-sectional study investigated attitudes toward mental illness of 146 registered nurses and mental health technicians in a psychiatric hospital. The study was guided by the Modified Labeling Theory. Respondents expressed stereotyping beliefs that people with mental illness would be devaluated and discriminated, and endorsed stigmatizing attitudes expressing stronger desire for social distance from a person with schizophrenia than depression or diabetes. Implications for future research, nursing education and practice are discussed.